Exploration of Digital Media and Parents' Perceptions of Gadget Integration as an Accelerator of Science Literacy for Students - Evita Rosilia Dewi (Global Education Journal, 2025)
Scientific literacy is a fundamental competence for students in Islamic Elementary Schools (Madrasah Ibtidaiyah/MI) to navigate the challenges of the Industrial Revolution 4.0 and Society 5.0. However, the mastery of scientific concepts is often hindered by the abstract nature of the material, which is difficult to visualize through conventional media. This study explores the utilization of digital media and analyzes parents' perceptions regarding gadget integration as a science literacy accelerator at MI Unggulan Miftahul Huda Gerih. A qualitative descriptive approach with a case study design was employed, utilizing observation, in-depth interviews, and documentation for data collection. The results indicate that digital media, such as interactive simulations and educational videos, effectively clarify abstract scientific concepts and significantly enhance students' scientific inquiry. Furthermore, parents have begun to perceive gadgets as essential cognitive tools, although concerns regarding non-educational content remain a primary challenge. This study emphasizes the necessity of synergy between a technology-based curriculum and proactive parental support. It underscores the importance of digital literacy for both teachers and parents to optimize science education quality in the madrasah environment.